PL004: A population-based analysis of outcomes in patients with a primary diagnosis of hypertension in the emergency department, using linked datasets. (2nd June 2016) - Masood, S.; Atzema, C.L.; Austin, P.
Abstract : Introduction: Patients seen primarily for hypertension are common in the emergency department. The outcomes of these patients have not been described at a population level. In this study we describe the characteristics and outcomes of the patients making these visits, as well as changes over time.Methods: This retrospective cohort study used linked health databases from the province of Ontario, Canada, to assess emergency department visits made between April 1, 2002 and March 31, 2012 with a primary diagnosis of hypertension. We determined the annual number of visits as well as the age and sex standardized rates. We examined visit disposition and assessed mortality outcomes and potential hypertensive complications at 7, 30, 90, 365 days and 2 years subsequent to the ED visit.Results: There were 206, 147 qualifying ED visits from 180 sites. Visits increased by 64% between 2002 and 2012, from 15793 to 25950 annual visits, respectively. The age- and sex-standardized rate increased from 170/100, 000 persons to 228/100, 000 persons over the same time period, a 34% increase. Eight percent of visits ended in hospitalization, but this proportion decreased from 9.9% to 7.1% over the study period. Mortality was very low, at less than 1% within 90 days, 2.5% within 1 year, and 4.1% within 2 years. Among subsequent hospitalizations for potential hypertensive complications, stroke was the most frequent admitting diagnosis, but the frequency was still <1% within 1 year. Together hospitalizations for stroke, heart failure, acute myocardial infarction, atrial fibrillation, renal failure, hypertensive encephalopathy and dissection were <1% at 30 days.Conclusion: The number of visits made primarily for hypertension has increased dramatically over the last decade. While some of the increase is due to aging of the population, other forces are contributing to the increase. Subsequent mortality and complication rates are low and have declined. With current practice patterns, the feared complications of hypertension are extremely infrequent.